The effect of training and duration of surgery on adhesion formation in the rabbit model - Ordoñez, J.L. (1997)
In order to evaluate the effect of training upon postoperative adhesions, standard bipolar and mechanical, nonopposing injuries were performed in the uterine horns and side walls of 52 mature female rabbits using a conventional three-puncture laparoscopy, by an endoscopic surgeon with limited experience. An additional injury, either bipolar or mechanical or both, was performed in the retro-uterine space. With experience, the duration of surgery decreased progressively from 12 K 2 to 8 K 1 min in the first and last 10 animals respectively. The amount of perioperative bleeding was not affected by experience. With experience the postoperative adhesions decreased in extent (P J 0.0001), tenacity (P J 0.004), type (P J 0.002) and inflammation (P J 0.003) and for total score (P J 0.0002). These changes were correlated with the briefer duration of surgery but not with the amount of perioperative bleeding. The strong correlations of adhesion scores in the pouch of Douglas, and around both uterine horns confirmed the importance of the inter-animal variability in making adhesions. By logistic regression, the adhesions in the pouch of Douglas were explained simultaneously by the adhesions on the uterine horns (P J 0.0004, thus correcting for interanimal variability) by the amount of bleeding (P J 0.01) and the duration of surgery (P J 0.05). No major differences were found in adhesions following a mechanical or a bipolar injury or following such a lesion in the pouch of Douglas or at the uterine horns. In conclusion, experience, expressed by the duration of surgery and to a lesser extent perioperative bleeding, is a major co-factor in postoperative adhesions, suggesting that duration of surgery should be strictly standardized in endoscopic adhesion studies. The important inter-animal variability can be circumvented by using a standard control lesion, making each animal its own control.